Multi-criteria optimization of green hydrogen hubs in Türkiye with integration to the Asia-Europe hydrogen corridor - Celikdemir, Soner; Ozdemir, Mahmut Temel (Pergamon-Elsevier Science Ltd, 2026)
This study conducts a nationwide spatial assessment of T & uuml;rkiye's green hydrogen production hubs and integrates these hubs with prospective international hydrogen corridors through a multi-criteria decision-making framework that combines the Starfish Optimization Algorithm (SFOA) with Monte Carlo simulation. A new model is developed by linking the Optimized Routes and Basins for International Transfer framework with the Pipeline Route Integration for Multinational Energy model, enabling both the identification of provincial scale hydrogen hubs and the analytical evaluation of their potential connectivity to emerging Asia-Europe energy transmission routes. The hybrid SFOA-Monte Carlo model is applied to 81 provinces and nine load dispatch regions using twelve criteria that capture renewable energy potential, infrastructure accessibility, and demand characteristics. The normalized provincial scores range from 0.08 to 0.57, with a national mean of 0.29 +/- 0.11. I(center dot)stanbul exhibits the highest potential (0.57), driven by strong energy generation capacity, logistical accessibility, and favorable conditions for international integration. The model achieves a convergence coefficient above 0.95 and an average error rate below 1.7 %, demonstrating strong numerical stability. The results indicate the emergence of an east-west-oriented hydrogen backbone, suggesting that spatially robust hub clusters may form the analytical basis for a future Asia-Europe hydrogen energy bridge. Overall, the framework functions as a quantitative decision-support tool for guiding both national and continental-scale hydrogen planning during T & uuml;rkiye's transition toward a sustainable hydrogen economy.
Keywords: Green hydrogen hubs; Starfish optimization algorithm; Monte Carlo simulation; Multi-criteria decision making; Asia-Europe hydrogen corridor